Leveraging multinational enterprises to reduce the escalating regional carbon inequality in China - Kailan Tian; Yu Zhang; Jing Meng; Zhuoying Zhang; Yuli Shan; Heran Zheng; Xiaowei Nie; Cuihong Yang (Nature Communications)
Abstract Multinational enterprises (MNEs) affect regional inequality as they exert substantial yet uneven economic and environmental effects. This study evaluates the impacts of MNEs on China’s regional carbon emission inequality against value-added gains using an environmentally extended interprovincial input-output model that differentiates MNEs activities across China’s provincial-level administrative divisions. We find that MNEs predominantly concentrated in developed coastal regions from 1997–2012, while less developed inland regions accounted for less than 30% of MNEs-generated value-added but over 50% of MNEs-related carbon emissions. This imbalance exacerbated regional inequality during this period. A pivotal change occurred over 2012–2017 as MNEs increasingly relocated inland and expanded their presence in clean technology-intensive industries, significantly reducing regional inequality. We also highlight the potential of leveraging MNEs’ knowledge spillovers to mitigate emissions and inequality. These insights offer policy implications for strategically deploying MNEs to address inequality and climate change, aligning with Sustainable Development Goals.